Making secondary education relevant for all: reflections on science education in an expanding sub-sector. Issue 6 (2nd November 2017) - Barrett, Angeline M.
Abstract: This think piece focuses on relevance in secondary science education to propose a research agenda for contexts in sub-Saharan Africa, where enrolments are expanding from a low base. The notion of sustainable work is used to consider what kind of science education is relevant for students who will continue to become science specialists and those who will apply their science knowledge in non-specialist paid and unpaid roles. Drawing on insights from the literature on science and indigenous knowledge, on education for sustainable development and sociolinguistic analysis of science classrooms, it is argued that making connections between informal and formal knowledge is essentially the work of secondary education. Understanding secondary education in these terms highlight its vital contribution to addressing sustainable development, which at its heart recognises the interconnectedness of human and natural systems.